Cinematic Orientalism: East-West Perception in Netflix's 'Swimmers' - Kemal Çelik (Medya ve Kültür)
This article analyzes the movie "The Swimmers" using ideological and frame-by-frame film analysis methods. The themes, characters, and locations in the film are evaluated in the context of the critique of orientalism and self-orientalism, analyzing how ideological themes are processed and reinforced. The film associates concepts of faith and hope with Christianity, presenting Christian characters as saviors. While telling the story of Syrian refugees, the film chooses Christian and European-looking heroes, portraying Muslims negatively. Emphasizing the superiority of Western culture, the film depicts the Eastern world as backward and helpless. Countries such as Turkey are coded as dark and uncanny, while European countries are idealized. The positive portrayal of Greece praises European efforts towards refugees but creates a negative image of the Turkish Coast Guard. The orientalist and self-orientalist elements of the film are attempts to present an attractive narrative for Western audiences. The Muslim screenwriter's distortion of Eastern historical realities under Western producers' influence represents self-orientalism. This approach reflects an endeavor to present Eastern culture in line with Western perspectives to gain Western approval, reinforcing prejudices rather than fostering understanding of cultural and political differences.